Intravaginal Misoprostol versus Transcervical Foley Catheter for Pre-Induction Cervical Ripening and their Outcome - A Comparative Study (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective : To compare the efficacy of transcervical Foley Catheter and Intravaginal Misoprostol in pre-induction cervical ripeningMaterials & Methods : This crosssectional study was done in the inpatient dept. of obs. and gynae at the Rangpur Medical College and Hospital, Rangpur, Bangladesh between 1st July 2005 to 30th December, 2006. During 18 (eighteen) months of study period, 99 patients were enrolled, 50 were in group 1 where Misoprostol tablet was given vaginally and 49 were in group II where Foley Catheter was used transcervically. The Misoprostol tablet dosing regime was 50?g (one- fourth of a 200?g tablet), which was given vaginally (in the posterior vaginal fornix). The second dose was given after six hours. Though the maximum target was four doses that was 200?g, cervical ripening took place in all the cases with only two doses. Cervical scoring was reassessed after four hours in both the groups.Results: There were similar baseline characteristics such as age of the patients, socioeconomic condition etc. No significant difference was observed regarding parity, gravidity, gestational age, Bishops score and pre-induction of labour. There was also no significant difference in the mean time of pre-induction to delivery interval, mode of delivery and neonatal out come. Change in Bishops score was similar in both groups but more time was required from pre-induction to delivery in Foley catheter group. The most frequent complaint in Foley catheter group was mild discomfort at insertion. Vaginal delivery was higher in this group (63.3%) whereas Caesarean section rate was higher in Misoprostol group (36%) due to hyperstimulation syndrome.Conclusion: Both intravaginal Misoprostol and transcervical Foley catheter have similar effectiveness as pre-induction agents in unripe cervix. Transcervical Foley catheter is associated with a lower incidence of hyperstimulation syndrome (presence of hypertonous utrine contraction associated with abnormal foetal heart rate) and higher incidence of vaginal deliveries.Bangladesh J Obstet Gynaecol, 2012; Vol. 27(2) : 72-78